Peningkatan Administrasi Pembukuan Pada Bank Sampah “Sami Berkah” Kel. Meteseh, Kec. Tembalang , Semarang - Heru Yulianto; Endang Dwi Wwhyuningsih; Dimas Adi Wicaksono; Aniqotunnafiah Aniqotunnafiah; Mabrur Ismail; Muhamad Indra Yudi Setiawan (Perigel: Jurnal Penyuluhan Masyarakat Indonesia, 2024)
Bookkeeping administration is an important aspect in waste bank activities because it has the benefit of recording and carrying out complete and detailed reporting within a certain time period, so that there are no differences in calculations between customers and the Waste Bank management. The importance of bookkeeping administration in managing the Waste Bank (recording the entry and exit of each type of waste managed by the Waste Bank), can help optimize waste management and increase the effectiveness of waste management. Simple bookkeeping (in the form of Socialization) was introduced in the transaction cycle at the Bank Sampah "Sami Berkah", Kelurahan Meteseh, Kecamatan Tembalang, Semarang (making a Chart of Account, Journal from proof of transactions, posting to the ledger and subsidiary books, up to making Financial Reports). The administrative management of the Bank Sampah Sami Berkah has met the minimum requirements of the Dinas Lingkungan Hidup, starting from books, officers, waste reception schedules, until the waste deposited has been sorted by customers/members. Likewise, the duties and responsibilities of waste bank management officers are in accordance with the job and description of the organizational structure. The proposed use of the information system at the "Sami Berkah" Waste Bank is the use of an Android-based application or web system (mobile web access) in order to accommodate the need for faster and easier information access for customers/Members and Waste Bank managers, as well as being able to overcome the Bank's operational problems. Waste starts from customer registration, savings transaction processes to reporting, efficiently and with integrity. and easy to manage by admins and monitored by users directly.